Fractals and Nonlinearity of Ocean Waves - Harman Ajiwibowo (Jurnal Teknik Sipil, 2003)
Abstract. From observations using secondary field data and dimension calculations, ocean waves exhibit fractals. Fractals are also hypothesized to have a direct relation with the degree of the waves nonlinearity. We tooksecondary data of 40 time series of wave record taken from Grays Harbor Wave Refraction Experiment, Washington in 1999. The data are divided into two groups, one group being data taken from the water depth of 25 meters and second group being data taken from water depth of 12 meters. The selection of data is in such a way that the second group is the waves traveling from the first group. We use rescaled range analysis to calculate the fractal dimension of the waves and Goda nonlinearity parameter as a measure of the waves nonlinearity. From the results, we confirm that fractals are a function of waves nonlinearity.Abstrak. Dari data sekunder dan perhitungan dimensi, gelombang laut mempunyai karakteristik fraktal. Bentuk fractal dari gelombang laut diasumsikan mempunyai hubungan langsung dengan ketidaklinearan dari gelombang laut. Untuk pembuktian asumsi ini diambil data pengamatan 40 data seri waktu yang diambil dari eksperimen refraksi di Grays Harbor, Washington tahun 1999. Data ini dibagi menjadi 2 grup, grup pertama adalah data yang diambil di perairan dengan kedalaman 25 meter dan grup kedua diambil dari data yang diambil di perairan dengan kedalaman 12 meter. Pengambilan data di grup kedua adalah sedemikan rupa sehingga data ini adalah berasal dari gelombang yang berjalan dari data grup pertama. Setelah dilakukan perhitungan dimensi kurva dengan menggunakan Analisa Rescaled Range dan mengambil parameter Goda sebagai ukuran ketidaklinearan gelombang laut, didapati bahwa bentuk fraktal gelombang laut berhubungan langsung dengan ketidaklinearan gelombang.